2004
DOI: 10.1021/ja045577l
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-Based Photonically Switched Half-Adder

Abstract: A molecule-based binary half-adder with optical inputs and outputs has been demonstrated. The half-adder consists of two photochromic organic molecules in solution and a third-harmonic-generating crystal. One substance acts as an AND Boolean logic gate and the other as an XOR gate. Inputs are laser pulses at 1064 or 532 nm that initiate photoisomerization reactions. Outputs are the optical absorbance of a fullerene radical anion (AND gate) and fluorescence of a porphyrin (XOR gate). The system carries out bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 18 publications
1
105
0
2
Order By: Relevance
“…Arithmetic operations require combinations of two or more logic gates that carry out addition or subtraction. A number of molecular half-adders [1][2][3][4][5][6][7] and half-subtractors 4,5,8,9 have been described, or discussed theoretically. 10,11 These function through chemical inputs (e.g., acid, base, ions) that cause the switching operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arithmetic operations require combinations of two or more logic gates that carry out addition or subtraction. A number of molecular half-adders [1][2][3][4][5][6][7] and half-subtractors 4,5,8,9 have been described, or discussed theoretically. 10,11 These function through chemical inputs (e.g., acid, base, ions) that cause the switching operations.…”
Section: Introductionmentioning
confidence: 99%
“…One chromophore is a spiropyran (1), and the other two are identical quinoline-derived dihydroindolizines (2 Figure 2). Although the details of the kinetic processes are complex, the overall concept is simple: Irradiation at 355 nm leads to net isomerization in the direction of the arrows in Figure 2, whereas thermal reversion results in net isomerization in the opposite direction.…”
mentioning
confidence: 99%
“…By using light of carefully selected wavelengths in the UV and the visible region of the spectrum, the independent isomerization of the photochromes Indeed, by the use of three photonic inputs in the UV (302 nm, 366 nm, and 397 nm) and two in the visible (green light and red light), together with output readings at five different wavelengths, we showed that the triad can perform the functions of 13 logic devices. These include the half-adder, [56][57][58] half-subtractor, multiplexer, [16] demultiplexer, [15] encoder, [18] decoder, [18] keypad lock, [21] and reversible logic gates. [23,59,60] Moreover, all functions were operated with one common initial state (FGo-DTEo), many of them in parallel and all of them resettable by the universal application of green light (see Scheme 5).…”
Section: All-photonic Switching As Idealized Approach Toward Moleculamentioning
confidence: 99%
“…Most circuits implemented in laboratory experiments so far are one-bit half-adders. Half-adders and their component gates are realised using enzymatic networks [38,33,10,30,27], photonic molecular devices [7,8,25], quantum logic inside a single molecule [18], molecular structural circuits [19,32], acellular slime mould [40,3,28,41], nuclear magnetic resonance [36], ribosomes and mRNAs [35], peptide networks [9], and excitable chemical media [23,21,16,22]. In excitable chemical media signal careers are excitation waves; the signals are modified via interaction between the excitation waves or wave-fragments.…”
Section: Introductionmentioning
confidence: 99%